56.9k views
0 votes
14. Solve for the value of x in this equation.
2x - (4x + 1) = 3x - 6

2 Answers

0 votes

Answer:

-1.4 = x

Explanation:

Step 1: Combine like terms and subtract the 3x from 2x.

-x - (4x + 1) = - 6

Step 2: Combine more like terms. (and remove parentheses)

-5x + 1 = - 6

Step 3: Combine different like terms.

-5x = -7

Step 4: Divide it out.

x = - 1.4

User InfiniteFlash
by
5.2k points
0 votes

Explanation:

2x-(4x+1)=3x-6

  • 2x-4x-1=3x-6
  • -2x-1=3x-6
  • 3x+2x=6-1
  • 5x=5
  • x=5/5
  • x=1
User Arenim
by
6.0k points